Model of Buddhism-Based Learning to Enhance the Compassionate Mind of Higher Education Students - Muangkaew, Kasamas; Boonsriton, Parud; Mangkhang, Charin; Dibyamandala, Jarunee (Community and Social Development Journal, 2024)
The purposes of this research were: to synthesize elements and indicators of the compassionate mind of higher education students, to develop a model of Buddhism-based learning to enhance the compassionate mind of higher education students; and to study the implementation results of a model of Buddhism-based learning to enhance the compassionate mind of higher education students. Key informants were selected by purposive sampling. The instruments used were: a semi-structured interview form which data were analyzed through content analysis and summarized into issues, a model verifying form which the data were analyzed using frequency and percentage; and a satisfaction form and model evaluation form which the data were analyzed by mean and standard deviation. The research results showed that the results of synthesizing elements and indicators of the compassionate mind of higher education students consisted of five preliminary elements and twenty-one indicators, a complete model of Buddhism-based learning to enhance the compassionate mind of higher education students was POO(LLOTUSS)D, the accuracy and suitability of this model were at the highest level; and results of studying the implementation results of a model of Buddhism-based learning to enhance the compassionate mind of higher education students were overall at the highest level.